Analyze Costs and Financial Return of Phoenix Oyster Mushroom Cultivation Process of Farmers in Pakchong Sub-district Chombueng District Ratchaburi Province (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were to: 1) investigate the cost and yield of Phoenix Oyster Mushroom cultivation, and 2) use as a guideline for those who were interested in cultivating the Phoenix Oyster Mushroom. The sample of this research was a group of 30 Phoenix Oyster Mushroom cultivators at Pak Chong sub-district, Chom Bueng district, Ratchaburi province. An in-depth interview was used to collect data for this qualitative research. The respondents’ opinions towards the Phoenix Oyster Mushroom cultivation were analyzed and synthesized using the content analysis statistics in relevant with the facts of the key issues. The results revealed that the respondents included 20 female and 10 male with an average age of 45 years old. The respondents have been engaging in the Phoenix Oyster Mushroom cultivation business between two to thirteen years. Hungarian and Bhutanese Phoenix Oyster Mushroom were the major types that the respondents cultivated and that of they produced their own mushroom compost. The mushroom cultivation period from the beginning stage until harvesting last around one month or forty-five days. Each household owned four houses of mushroom cultivation. In terms of production, each house could yield around one thousand kilograms which its selling price was between 80 to 120 baht per kilogram. The cost of mushroom cultivation was 34, 341.25 baht per house while it yielded worth around 45,125 baht. The production of each house was unequal based on the integrity of the mushroom compost, the weather, and the green mold disease (Trichoderma harzianum Rifai)..